La fecundidad de los grupos étnicos en México - Vázquez Sandrin, Germán (El Colegio de México A.C., 2019)
The article serves two main purposes: on the one hand, it shows the variety of levels of indigenous fertility at the most disaggregated scale possible in contemporary Mexico; and, on the other, it validates the hypothesis that considers that at least some ethnic groups maintain their own fertility.  The results of the article show an interethnic diversity of fertility levels that vary between 1.7 and 5.6 children per woman, and identify 25 indigenous groups whose fertility has a cultural or other kind of specificity, which are relevant in explaining fertility in Mexico.